Structural, Optical and photoluminescence Properties of Nanocrystalline NiO Thin Films - Abbas, Sabah Ibrahim; Ubaid, Ahmed Qasim (JOURNAL OF ADVANCES IN PHYSICS, 2014)
Thermal chemical spray pyrolysis technique has been successfully employed for deposition of nanocrystalline nickel oxide(NiO) thin films from hydrated nickel chloride salt solution on the glass substrate at temperature 450°C. The structuralproperties of nickel oxide films were studied by means of X-ray diffraction (XRD) and scanning Probe Microscope (SPM). XRD analysis shows that the film is polycrystalline nature with cubic structure along (111) orientation centered at 37.23°. The crystallite size was evaluated to be 21.63 nm by using Scherrers equation. The morphology and crystallite size wasevaluated by using Atomic Force Microscope (AFM) images showed spherical shape particles on the surface areinhomogeneous and very smooth on the nanometer scale. The optical absorption spectra were taken to determine the band gap 3.8 eV, increase in band gap energy is revealed that nanostructure films. The photoluminescence spectrum of these samples were an excited at wavelength 250 nm and consist of the emissions band located at 240 nm, 370 nm, and 492 nm.